Investigation of FADS Gene Cluster Single Nucleotide Polymorphisms in End-Stage Renal Disease Compared With Normal Controls - Miladipour, Amirhossein; Gholipour, Mahdi; Honarmand Tamizkar, Kasra; Abak, Atefe; Kholghi Oskooei, Vahid; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Genetics, 2021)
End-stage renal disease (ESRD) is a public health problem with a high burden. The condition is associated with abnormalities in lipid metabolism. The fatty acid desaturase (FADS) gene cluster includes three genes that are significantly correlated with a number of pathologic conditions related to abnormal lipid levels. In the current study, we genotyped rs174556, rs99780, and rs7115739 single nucleotide polymorphisms within the FADS cluster in a population of ESRD patients and healthy controls. The rs174556 of the FADS1 gene and rs99780 of the FADS2 gene were not associated with the risk of ESRD in any inheritance model. However, the rs7115739 of FADS3 was associated with the risk of ESRD in all models except for the recessive model. The T allele of this SNP was significantly less prevalent among cases compared with controls [odds ratio (OR) (95% CI) = 0.44 (0.25–0.77), P value = 0.004]. GT and TT genotypes has been shown to decrease the risk of ESRD in a codominant model [OR (95% CI) = 0.49 (0.26–0.92) and OR (95% CI) = 0.18 (0.02–1.6), respectively; P value = 0.019]. In the dominant model, GT + TT status was associated with lower risk of ESRD [OR (95% CI) = 0.45 (0.24–0.82), P value = 0.0078]. Assessment of association between this SNP and risk of ESRD in an overdominant model revealed that GT genotype decreases the risk of this condition [OR (95% CI) = 0.5 (0.27–0.94), P value = 0.029]. Taken together, the rs7115739 of FADS3 is suggested as a putative modulator of the risk of ESRD in the Iranian population.